2020
DOI: 10.3390/su12176787
|View full text |Cite
|
Sign up to set email alerts
|

Resources Confirmation for Tourism Destinations Marketing Efforts Using PLS-MGA: The Moderating Impact of Semirural and Rural Tourism Destination

Abstract: This study presents a framework to empirically validate the relationship between the tangible and intangible measures on tourism destination marketing efforts. Uniquely, a case study was developed involving two different nature of tourism destinations (semirural and rural) and is incorporated into the framework to assess its moderating effect on the relationships among the predictors and destination marketing efforts. Two hundred and ninety-three usable responses were collected using a questionnaire survey. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 81 publications
0
15
0
Order By: Relevance
“…Regarding composite reliability (CR), it is an indicator similar to Conbrach's alpha that is more appropriate in structural equations. Results showed that all reliability values reached the required levels (λ ≥ 0.70, CR ≥ 0.70) [114] (Table 3). Therefore, it was accepted that the measurement model was internally consistent and that all the observed variables were measuring their corresponding construct [117].…”
Section: Test Of the Measurement Modelmentioning
confidence: 89%
See 1 more Smart Citation
“…Regarding composite reliability (CR), it is an indicator similar to Conbrach's alpha that is more appropriate in structural equations. Results showed that all reliability values reached the required levels (λ ≥ 0.70, CR ≥ 0.70) [114] (Table 3). Therefore, it was accepted that the measurement model was internally consistent and that all the observed variables were measuring their corresponding construct [117].…”
Section: Test Of the Measurement Modelmentioning
confidence: 89%
“…Moreover, it is unnecessary to assume a normal distribution of data when using PLS [112]. The ultimate guidelines in applying PLS-SEM in tourism research have been followed, and an Importance-Performance Analysis (IPMA) has been included [113,114].…”
Section: Discussionmentioning
confidence: 99%
“…The results of the MICOMs (Table 11) showed that the means and variances of composites across the two groups do not differ, and thus a full measurement invariance criterion could be established. Thus, meeting the three requisites, we can establish that the two groups are suitable for analysis using the MGA method [75,76]. Concerning the reliability of both models, the Cronbach's alpha and the CRI of the OCB variable when testing the high purpose implementation group were 0.841 and 0.904, respectively [62,63].…”
Section: Testing the Hypothesismentioning
confidence: 98%
“…The interventions can be categorised into two main policies, including (i) increasing the diagnostic testing, improving the clinical producers, and rapid isolation of confirmed cases [4]; and (ii) restriction of mobility in global, national, and regional levels [5]. The tourism industry is one of the most affected sectors by COVID-19 [6], as most countries have implemented entry restrictions on all foreign nationals in response to the COVID-19 outbreak [5,7]. Consequently, international tourism slowed down by 22% in the first quarter of 2020, and the number of international tourists is forecasted to drop by 60-80% in 2020 [8].…”
Section: Introductionmentioning
confidence: 99%
“…Although the negative impacts of COVID-19 on economic, employment, and household income are unknown to date [6], negative relationships exist between the development Sustainability 2021, 13, 1553 2 of 20 of international tourism and pandemic outbreaks [1]. Consequently, a loss of 75 million tourism industry jobs is estimated in 2020 [8].…”
Section: Introductionmentioning
confidence: 99%